2018
DOI: 10.22190/fume180108007c
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Mechanics Simple Calculations to Explain Small Reduction of the Real Contact Area Under Shear

Abstract: Abstract. In a very recent paper, Sahli and coauthors [12] (R.Sahli

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 21 publications
3
18
0
Order By: Relevance
“…friction, plasticity, dislocation emission) and cannot be ascribed to a single phenomenon [16]. Since then, a few phenomenological models have been proposed ( [17], [18], [19], [20], [21], [22], [23]) which require a Mode-Mixity Function (MMF) f (ψ) [26] to describe the critical condition for propagation G c = G Ic f (ψ) (1) where G Ic is mode I critical factor (or surface energy, if we assume Griffith's concept), G c is the critical energy release rate in mixed mode conditions and finally ψ is the "phase angle"…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…friction, plasticity, dislocation emission) and cannot be ascribed to a single phenomenon [16]. Since then, a few phenomenological models have been proposed ( [17], [18], [19], [20], [21], [22], [23]) which require a Mode-Mixity Function (MMF) f (ψ) [26] to describe the critical condition for propagation G c = G Ic f (ψ) (1) where G Ic is mode I critical factor (or surface energy, if we assume Griffith's concept), G c is the critical energy release rate in mixed mode conditions and finally ψ is the "phase angle"…”
Section: Introductionmentioning
confidence: 99%
“…Experimental measurements of contact area evolution show that the shape of contact area is circular, according to JKR theory, at zero tangential force and shrinks in an elliptical-like fashion while the shear force is increased ( [8], [15], [19]). So far, all LEFM models proposed ( [14], [17], [18], [19], [22], [23]) make the approximation to consider the contact as circular, even when sheared. This requires an averaging of the effects of mode II and mode III around the periphery.…”
Section: Introductionmentioning
confidence: 99%
“…the effective surface energy (or toughness of the interface) is increased, rather than decreased in Savkoor's theory (5), and curiously of a very similar quantity, perhaps even exactly the same since τ 0 = τ m , if Y = 2 π . This should not be confused from the result of the theories using the mode-mixity functions of the type (1), like (Ciavarella, 2018, since in the latter case, there is no size-effect associated to the contact area a, as there is in (13), and this has profoundly different implications, as we shall explore.…”
Section: The Area Enhancement MCD Theorymentioning
confidence: 82%
“…In particular, Johnson (1997) attempts also to model slip explicitly with cohesive models (as well as the mode I corresponding part), and even in this case, the conclusion remains of the contact area reduction. Various recent other papers (Ciavarella, 2018 have shown that the size and even the elliptical shape of the contact under shear are reasonably found by these LEFM models over a wide range of loads and geometrical features, despite the mixed-mode function strictly requires a complex functional form to replicate faithfully the results and hence empirical fitting at least over one set of results. Also, they suggested there is no obvious advantage in trying to model the slip displacements (which correspond to recur to a cohesive model, in the context of fracture mechanics), since this effect is essentially included in the mixed-mode function.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation